Odpowiedzi

2010-01-26T18:35:12+01:00
A) -2 -2 + 3=-1
b)2a - 3b + 3a - 2b=5a-5b
c)2y - 6y + 4x - 2x=2x-4y
d)2x + 3 - 6x - 10=-4x-7
e) -x + 2x + (-6) + x - 4=2x-10
f) 2ab - 6 - ab - (-3)=ab-3
g) 3x² - 2y²- 6x² - 2y²=-3x²-4y²
h) 3,5b - 2,4c - 0,6c - 0,5b=3b-3c
1 4 1
Najlepsza Odpowiedź!
2010-01-26T18:37:50+01:00
A) -2 -2 + 3 = (-1)
b)2a - 3b + 3a - 2b = 5a - 5b
c)2y - 6y + 4x - 2x = 2x - 4y
d)2x + 3 - 6x - 10 = (-7) - 4x
e) -x + 2x + (-6) + x - 4 = 2x - 10
f) 2ab - 6 - ab - (-3) = ab - 3
g) 3x² - 2y²- 6x² - 2y² = (-4)y² - 3x²
h) 3,5b - 2,4c - 0,6c - 0,5b = 3b - 3c
1 4 1
2010-01-26T18:39:00+01:00
A) -2 -2 + 3= -1
b)2a - 3b + 3a - 2b= 5a-5b
c)2y - 6y + 4x - 2x= 2x-4y
d)2x + 3 - 6x - 10=-7-4x
e) -x + 2x + (-6) + x - 4= -10+2x
f) 2ab - 6 - ab - (-3)=-3+ab
g) 3x² - 2y²- 6x² - 2y²=-3x²-4y²
h) 3,5b - 2,4c - 0,6c - 0,5b=3b-3c
1 4 1